Deteksi Candida albicans pada urin wanita penghuni lembaga pemasyarakatan perempuan kelas IIA Sungguminasa - Sulfiani; Nurzaswasila; Hartati (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2024)
Candida albicans is a member of the normal flora found in the mocous membranes, digestive tract, respiratory tract, urethera, vagina, skin and nails of the hands and feet. Candida albicans can grow at various pH levels, but generally, growth will be better at a pH between 4,5-6,5. The type of research used qualitative descriptive research. This research aimed to detect Candida albicans fungus in the urine of women inmates at the Sungguminasa Class IIA Women’s Penitentiary with symptoms vaginal discharge. Reproductive health problems in women that need attention are reproductive tract infections, one of which is vaginal discharge. 75%  of women in the world have experienced vaginal discharge at least once in their lifetime. This research was conducted at the Sungguminasa Class IIA Women’s Prison. The samples were taken from 11 respondents in the form of the urine of the women who were experiencing vaginal discharge, then inoculated on SDA media which had been added with chloramphenicol and then incubated at 37oC for 7 days. The results was a ccolony that had the characteristics of Candida albicans fungus based on macroscopic observations, namely round shape, white cream color, and soft texture. Slightly wrinkled in old colonies, the surface was raised and there was a characteristic yeast smell. Determination of microsopic morphology. Colony preparations were made using gram staining and then observed under a microscope with 10x10 magnification. The research results showed that 6 samples were positive for c. albicans, and 5 samples were negative for C. albicans.